Mixed adenoneuroendocrine carcinoma of the gastric stump following Billroth II gastrectomy: case report and review of the literature - Cazzo, Everton (2016)
CONTEXT: Gastric stump cancer after gastric resection is a well-known disease. It may be a newly de- veloped cancer after resection due to benign disease, or recurrent or residual disease after oncological surgery. The predominant histological type is usually adenocarcinoma. This study aimed to report on a rare occurrence of a mixed adenoneuroendocrine carcinoma (MANEC) on the gastric stump. CASE REPORT: The case of an 83-year-old female who presented a locally aggressive gastric stump MANEC, 35 years after Billroth II gastrectomy to treat a peptic ulcer, is reported. The patient underwent resection and adjuvant therapy. She has been followed up for one year without signs of recurrence. CONCLUSION: MANEC is a rare type of gastrointestinal neoplasm. The classification, histopathology, clini- cal features, treatment issues and prognosis are discussed along with a brief review of the literature.